An Investigation of Two Determinants of the Practice Effect in Tachistoscopic Word Recognition: Response Strength and Fixation - Hay, Janet M (My University, 1963)
Five experiments, involving 265 subjects, were performed with the objective of extending the analysis of response probability as a determinant of the practice effect in tachistoscopic word recognition. The results showed that the response probabilities of words may be manipulated and act as a determinant of the practice effect under certain limited experimental conditions. A more powerful determinant appears to be a general skill in tachistoscopic recognition which improves as a function of the number of stimuli recognized and transfers to the recognition of different stimuli. This skill was examined in the final experiment. The overall results were discussed in terms of both response probability and a general tachistoscopic skill.
An Investigation of the Practice Effect in World Recognition
Keywords: tachistoscopic word recognition, response strength and fixation, two determinants of the practice effect, practice effect, word recognition, practice effect in word recognition